2021
DOI: 10.3390/ma14247889
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hydrogen Generation Performance of Al-Rich Alloys by a Melting-Mechanical Crushing-Ball Milling Method

Abstract: The main problem for the application of hydrogen generated via hydrolysis of metal alloys is the low hydrogen generation rate (HGR). In this paper, active Al alloys were prepared using a new coupled method-melting-mechanical crushing-mechanical ball milling method to enhance the HGR at room temperature. This method contains three steps, including the melting of Al, Ga, In, and Sn ingots with low melting alloy blocks and casting into plates, then crushing alloy plate into powders and ball milling with chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…The efficiency of the developed catalyst was further compared in Table 1 with previous literature. [ 47–54 ] This revealed that Cu–Co/CH hydrogel may have more reactive sites and more quickly meet the NaBH 4 molecules and immediately generate H 2 gas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of the developed catalyst was further compared in Table 1 with previous literature. [ 47–54 ] This revealed that Cu–Co/CH hydrogel may have more reactive sites and more quickly meet the NaBH 4 molecules and immediately generate H 2 gas.…”
Section: Resultsmentioning
confidence: 99%
“…Before using it further, it was rinsed with distilled water. Figure 8 [47] CELL-EPC-DETA 2015 Sahiner and Demirci [48] Ag@CFC 2049 Ali et al [49] Co/Fe 3 O 4 @C 1403 Chen et al [50] Acid treated sepiolite 1486 Selvitepe et al [51] CF-A-CH 1179 Ali et al [52] FCell-PEI + 2308 Can et al [53] SCell-PEI+ 5520 Can et al [53] Al-3Ga-3In-3Sn 5337 Zhu et al [54] Cu Therefore, Cu-Ag/CH, Cu-Co/CH, and Cu-Ni/CH catalysts were utilized for complete reduction of 4-NP. Initially, when 0.05 g of each catalyst was added to 3 ml 4-NP + 0.5 ml NaBH 4 , then decrease in UV spectrum and loss of nitrophenolate ions colour was noticed.…”
Section: Recyclability Of Cu-co/ch Hydrogel Catalystmentioning
confidence: 99%
“…Aluminum ball milling together with oxides or hydroxides (Bi(OH) 3 , Al(OH) 3 , Al 2 O 3 , CaO, TiO 2 , etc. ), carbon-based materials (graphene, graphite, and carbon nanotubes) and salts (such as NaCl, KCl, NiCl 2 , and CoCl 2 ) is commonly used to reduce the particle sizes, destroy the oxide film, and create crystal lattice imperfections [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. The surface oxide layer can also be destructed during external loading.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have tried to find suitable physical or chemical methods to destroy the oxide layer on the aluminum surface [ 8 , 16 , 21 ]. Many works have proved high-energy ball milling to be an effective way for activating Al, which significantly increases the specific surface area and the defects on the powder surface [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, the surface protection of the ball milling Al-based composite powders is essential to prevent the formation of an Al 2 O 3 passivation layer.…”
Section: Introductionmentioning
confidence: 99%
“…A small amount of alloying elements can improve hydrogen production characteristics by modifying Al-based alloys’ microstructure and phase compositions [ 33 , 34 , 35 ]. In practical applications, Al-based composite powders are usually alloyed with metals, such as Bi, In, Ga, and Sn, to break the oxide layer and thus improve their hydrogen generation properties [ 22 , 25 , 28 , 29 ]. The low-melting point metals Bi and Sn easily form numerous holes, gaps, and other defects on the surface of Al, which increases the contact area between Al and water during hydrogen production by hydrolysis, thus improving the hydrogen production performance of the alloy [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%